The Effect of Good Corporate Governance on Earnings Management in Manufacturing Companies Listed on The Idx - Nuril Mufidah; Tuban Drijah Herawati (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2025)
Earnings management causes the presentation of financial statements to be irrelevant to the actual condition of the company. Earnings management carried out by managers can harm shareholders. Conflicts of interest and information asymmetry cause earnings management. One effort that can be made to prevent earnings management is through the implementation of good corporate governance. This study aims to test and obtain empirical evidence of the effect of good corporate governance with the proxy of managerial ownership, audit firm size, and audit committee on earnings management. This study uses a quantitative approach by collecting secondary data in the form of annual reports. The population studied was manufacturing companies listed on the IDX. The total sample was 55 companies selected using the purposive sampling method. The data analysis method used multiple regression analysis with the help of IBM Statistical Package for Social Science (SPSS) software. The results of the study indicate that audit firm size has a negative and significant effect on earnings management. Managerial ownership and audit committees do not have a significant effect on earnings management. This study shows investors and companies the importance of good corporate governance in reducing earnings management actions. Abstrak Manajemen laba menyebabkan penyajian laporan keuangan menjadi tidak relevan dengan kondisi perusahaan yang sebenarnya. Penelitian ini bertujuan untuk menguji dan memperoleh bukti empiris pengaruh good corporate governance dengan proksi kepemilikan manajerial, ukuran KAP, dan komite audit terhadap manajemen laba. Penelitian ini menggunakan pendekatan kuantitatif dengan melakukan pengumpulan data sekunder berupa laporan tahunan. Populasi yang diteliti adalah perusahaan manufaktur yang terdaftar di BEI. Total sampel adalah 55 perusahaan yang dipilih dengan metode purposive sampling. Metode analisis data menggunakan analisis regresi berganda dengan bantuan software IBM   Statistical   Package   for   Social   Science (SPSS). Hasil penelitian menunjukkan bahwa ukuran KAP memiliki pengaruh negatif dan signifikan terhadap manajemen laba. Kepemilikan manajerial dan komite audit tidak berpengaruh signifikan terhadap manajemen laba. Studi ini menunjukkan kepada investor dan perusahaan mengenai pentingnya good corporate governance untuk mengurangi tindakan manajemen laba.